2023
DOI: 10.3350/cmh.2023.0217
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Ion Radiotherapy in the Treatment of Hepatocellular Carcinoma

Hwa Kyung Byun,
Changhwan Kim,
Jinsil Seong

Abstract: Hepatocellular carcinoma (HCC) is a highly lethal cancer with limited treatment options and poor prognosis. Carbon ion radiotherapy (CIRT) has emerged as a promising treatment modality for HCC due to its unique physical and biological properties. CIRT uses carbon ions to target and destroy cancer cells with a high precision and efficacy. The Bragg Peak phenomenon allows precise dose delivery to the tumor while minimizing damage to healthy tissues. In addition, the high relative biological effectiveness of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“… 38 - 46 Furthermore, proton beam therapy (PBT) and carbon ion RT (CIRT) have been proven through various studies to provide outstanding disease control and acceptable toxicity. 19 , 22 , 25 , 47 - 64 Recent research has shifted focus toward the combined therapy of EBRT with other modalities or the potential of EBRT as an alternative to conventional local treatments in specific liver locations or depending on the patient’s condition and liver function. 65 - 68 Numerous comparative studies are being reported in this area.…”
Section: Efficacy Of Rt In Hccmentioning
confidence: 99%
See 3 more Smart Citations
“… 38 - 46 Furthermore, proton beam therapy (PBT) and carbon ion RT (CIRT) have been proven through various studies to provide outstanding disease control and acceptable toxicity. 19 , 22 , 25 , 47 - 64 Recent research has shifted focus toward the combined therapy of EBRT with other modalities or the potential of EBRT as an alternative to conventional local treatments in specific liver locations or depending on the patient’s condition and liver function. 65 - 68 Numerous comparative studies are being reported in this area.…”
Section: Efficacy Of Rt In Hccmentioning
confidence: 99%
“…In HCC treatment, CIRT has recently been recognized as a noteworthy therapeutic approach. 64 CIRT, a form of particle RT, leverages carbon ion beams for precise targeting and eradication of cancer cells. 64 The primary advantages of CIRT lie in its distinctive physical and biological characteristics.…”
Section: Particle Therapy For Hccmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle therapy that can be used in the management of HCC is mainly divided into proton beam therapy (PBT) and carbon ion RT (CIRT). 11,12 The main physical characteristics of particle therapy is the absorbed dose curve shows a slow initial increase with the penetration through matter, than a steep rise to the maximum, known as the Bragg peak, followed by a sharp fall in energy absorption toward the end of the beam range. 13 This unique characteristics can be able to provide a more precise dose delivery to the tumor, while minimizing radiation effect to the surrounding normal tissues effectively.…”
Section: Editorialmentioning
confidence: 99%